2013
DOI: 10.1152/ajpheart.00300.2013
|View full text |Cite
|
Sign up to set email alerts
|

Diverse regulation of IP3 and ryanodine receptors by pentazocine through σ1-receptor in cardiomyocytes

Abstract: Although pentazocine binds to σ1-receptor (σ1R) with high affinity, the physiological relevance of its binding remains unclear. We first confirmed that σ1R stimulation with pentazocine rescues contractile dysfunction following pressure overload (PO)-induced cardiac hypertrophy ovariectomized (OVX) female rats. In in vivo studies, vehicle, pentazocine (0.5-1.0 mg/kg ip), and NE-100 (1.0 mg/kg po), a σ1R antagonist, were administered for 4 wk (once daily) starting from the onset of aortic banding after OVX. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 31 publications
0
25
0
1
Order By: Relevance
“…There, the Sig-1R stabilizes IP3-activated IP3R preventing its degradation and allowing sustained calcium efflux towards the mitochondria to increase ATP production and maintain cell survival [49]. The chaperoning of IP3R by Sig-1R was shown to protect cells against stress in neurons [134][135][136][137][138] as well as cardiomyocytes [139,140]. Alteration of this mechanism has been linked with neurological disorders such as Huntington's disease [141], amyotrophic lateral sclerosis (ALS) [142,143], and cancer [144,145].…”
Section: Inositol 145-trisphosphate Receptor (Ip3r)mentioning
confidence: 99%
See 1 more Smart Citation
“…There, the Sig-1R stabilizes IP3-activated IP3R preventing its degradation and allowing sustained calcium efflux towards the mitochondria to increase ATP production and maintain cell survival [49]. The chaperoning of IP3R by Sig-1R was shown to protect cells against stress in neurons [134][135][136][137][138] as well as cardiomyocytes [139,140]. Alteration of this mechanism has been linked with neurological disorders such as Huntington's disease [141], amyotrophic lateral sclerosis (ALS) [142,143], and cancer [144,145].…”
Section: Inositol 145-trisphosphate Receptor (Ip3r)mentioning
confidence: 99%
“…The Sig-1R is targeted by many drugs that can be used to modulate IP3R calcium signaling. Indeed, the IP3R modulation by Sig-1R was shown to be reinforced by Sig-1R agonists and inhibited by antagonists in many different physiological and pathological cellular contexts [134][135][136][137][138][139][140][141]144,145]. Conversely, the Sig-1R can also modulate IP3R indirectly by stimulating IP3 production [148][149][150], increasing IP3R expression [151] and also by increasing Bcl-2 expression [152][153][154].…”
Section: Inositol 145-trisphosphate Receptor (Ip3r)mentioning
confidence: 99%
“…In fact, ROS production by peripheral cells 724 was shown to be inhibited by antipsychotic drugs such as risperidone 725 [14] or anti-cholesterol drugs, namely statins [86,87]. ER stress was 726 also shown to be affected by antipsychotic compounds [83]. Important- …”
mentioning
confidence: 99%
“…In the heart, IP3R2 contributes to the Ca 2+ influx into mitochondria and the Sig1R is physically associated with IP3R2. Interestingly, the Sig-1R stimulation by the agonists ameliorates cardiac hypertrophy and dysfunction through the enhancement of the Sig-1R-IP3R2 interaction and by restoring the IP3R2-mediated Ca 2+ mobilization from the ER into the mitochondria and the resultant mitochondrial ATP production [97, 98]. Recently, it was suggested that the RyR is involved in the cardiac protective effects of Sig-1R agonists [98, 99].…”
Section: Sig-1r-related Molecular Mechanisms and The Actions Of Cocaimentioning
confidence: 99%
“…Interestingly, the Sig-1R stimulation by the agonists ameliorates cardiac hypertrophy and dysfunction through the enhancement of the Sig-1R-IP3R2 interaction and by restoring the IP3R2-mediated Ca 2+ mobilization from the ER into the mitochondria and the resultant mitochondrial ATP production [97, 98]. Recently, it was suggested that the RyR is involved in the cardiac protective effects of Sig-1R agonists [98, 99]. Therefore, the Sig-1R may regulate a variety of intracellular Ca 2+ channels operated through both IP3Rs and RyRs, depending on the types of cells as well as the expression patterns of IP3R and RyR isoforms.…”
Section: Sig-1r-related Molecular Mechanisms and The Actions Of Cocaimentioning
confidence: 99%